Wearable technology: From the practice field to prime time - Shiffman, A.; Hawkins, A.; Holmes, S.; Wise, M.; Chao, D.; Madkour, A. (MIT Sloan Sports Analytics Conference 2016, 2016)
Wearable technology has progressed rapidly in recent years, with hardware getting smaller and more durable, software becoming more specialized and accurate, and analyses becoming more sophisticated. As technology has improved, the data and usefulness has increased exponentially, even allowing some elite athletes to migrate the use of their wearables from primarily training onto the field of play. This panel will discuss the current role of wearables in mitigating injury risk, the technological trends on the horizon, and in-game use as the next frontier for wearable technology.